Navigating Online Teaching: Teachers’ Challenges and Experiences as a Basis for Policy Development - Fernando, Madeline; Luis, Estrella; Luis , Janeth (Journal of Interdisciplinary Perspectives, 2025)
Online teaching has become an integral part of the educational landscape, continuing even beyond the pandemic. While research on online teaching has expanded, a gap remains in integrating teachers' practical challenges and experiences into policy development. This led to the conduct of this study, which aimed to explore the challenges and experiences encountered by teachers in online teaching, establishing a basis for policy development. In this study, a mixed-method approach was used, collecting quantitative data through surveys and qualitative data via open-ended questions and interviews. Participants were core and affiliate faculty from the Elementary Education department of Mariano Marcos State University (MMSU), Philippines. Experts validated the instruments, and the data were analyzed using descriptive statistics, as well as content and thematic analyses. Findings revealed that all participating teachers (100%) encountered varying challenges while delivering online instruction. Among these challenges, fostering class interaction and maintaining student motivation posed the most significant difficulty, with a mean score of 2.37. Connectivity and technical issues, as well as the demands of accomplishing teaching-learning tasks, were also identified as moderate challenges, both with a mean score of 2.23. Although personal and health-related concerns got the lowest mean score (1.92), they still contributed to the overall stress and difficulty of teaching online. Despite these challenges, teachers recognized the benefits derived from their online teaching experiences. The study's findings suggest the need for school policies to enhance internet accessibility, establish robust IT support systems, prepare teachers for online teaching, implement a system to monitor student participation, and promote a well-balanced work-life balance for teachers. By addressing these key areas, schools can create a more effective, supportive, and sustainable environment for online teaching and learning.